Status of Peace Club Activities in Public Secondary Schools within Kisumu County, Kenya (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
The occurrence of student unrest has been on the rise in Kenya and beyond. This has prompted the introduction of Peace Clubs in Kenyan schools. However, despite these efforts, many schools still experience student unrest. This study, therefore, sought to examine the status of Peace Club activities in schools. The study used a theoretical framework informed by contingency theory and integrative negotiations, and peer mediation theory. The study applied a descriptive survey research design with a sample size of 584 respondents. The researcher used focus group discussions, interviews, and questionnaires to collect primary data, while reviewed publications and reports from the County Director of Education office were used to obtain secondary data. The study applied to content and face validity checks to ascertain the relevance of the research data collection instruments, while reliability was ascertained using the split-half method. The data were then cleaned and coded using descriptive statistics, and the results were presented using frequency distribution tables, percentages, pie charts, and bar graphs. The study found that Peace Club activities didn't exist in most of the schools; most students didn't know about Peace Club activities. In schools where they existed, most of them were not active. It was concluded that the nonexistence and/or inactivity of Peace Clubs activities contributed to the student unrest experienced in schools. The study recommended a modification of the existing policy on the creation of Peace Clubs in schools and the conduction of regular supervision to ensure full implementation of Peace Clubs in schools.